Badlands [large type] - Lenhardt, Melissa (Lenhardt, Melissa. Sawbones series, 2018)
"Laura's worst fears have been realized: Kindle has been taken into custody and she is once again on the run. The noose awaits her in New York, but Laura is realizing that there are some things worse than death. Finally running out of places to hide, it may be time for Dr. Catherine Bennett to face her past"--